Effects of pleural drainage on oxygenation in critically ill patients. Issue 1 (10th March 2020) - Sakurai, Masako; Morinaga, Kentaro; Shimoyama, Keiichiro; Mishima, Shiro; Oda, Jun
Abstract : Aim: Pleural effusion is common among critically ill patients and associated with clinical consequences; however, the benefits of draining pleural effusion remain debatable. Thus, we aimed to investigate pleural drainage effectiveness by focusing on preprocedure patient status. Methods: We retrospectively analyzed 22 patients with pleural effusion. Gas exchange, ventilator settings, vital signs, inflammatory response, and nutrition status were examined preprocedure and 24 h and 1 week postprocedure. Data were analyzed using the non‐parametric test and discriminant analysis with receiver operating characteristic curves. Results: The partial arterial oxygen pressure (PaO2 ) to fraction of inspiratory oxygen (FI O2 ) (P/F) ratio at 24 h was higher postdrainage than predrainage (250 ± 87 versus 196 ± 84, P  < 0.05); however, no significant difference between the P/F ratio predrainage and 1 week postdrainage was noted. Patients were classified into effective and ineffective groups according to a 110% increase in the P/F ratio 1 week postdrainage compared with predrainage. The predrainage P/F ratio was lower in the effective group than in the ineffective group (165 ± 91 versus 217 ± 74, P  < 0.05). Discriminant analysis showed the area under the receiver operating characteristic curve was 0.72; the cut‐off value of the predrainage P/F ratio (divided into effective and ineffective groups) was 174. Conclusions: Pleural drainage could be effective in patients who have lower preprocedure P/F ratios. Abstract : The benefits of pleural drainage shown by focusing on patient state predrainage. The PaO2 to FI O2 (P/F) ratio was improved 1 day postdrainage and the P/F ratio was not improved 7 days postdrainage. Pleural drainage could be effective for patients with lower preprocedure P/F ratio.